2019
DOI: 10.21203/rs.2.9864/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic effect of vasoactive intestinal peptide on form-deprived amblyopic kittens

Abstract: Background Exploring the role of vasoactive intestinal peptide (VIP) in the lateral geniculate body (LGBd) in visual development and studying the therapeutic effect of VIP on amblyopic kittens. Methods Three-week-old domestic cats were divided into a control group (n = 10) and a monocular deprivation group (n = 20), with an eye mask covering the right eye of those in the deprived group. After pattern visual evoked potential (PVEP) recording confirmed the formation of monocular amblyopia, the left LGBd was i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For instance, amblyopia can induce paraptosis in visual cortical neurons [29], while VIP positive expression can inhibit the occurrence and development of amblyopia with antioxidant and anti-apoptotic activities [30,31]. Consistently, our previous studies found that amblyopia resulted in down-regulated VIP expression in the visual cortex of kittens with amblyopia [8], and that exogenous introduction of VIP increased the VIP expression in the visual cortex and elevated the PVEP amplitude [32]. Combining the ndings, VIP is critical to visual development.…”
Section: Discussionmentioning
confidence: 54%
“…For instance, amblyopia can induce paraptosis in visual cortical neurons [29], while VIP positive expression can inhibit the occurrence and development of amblyopia with antioxidant and anti-apoptotic activities [30,31]. Consistently, our previous studies found that amblyopia resulted in down-regulated VIP expression in the visual cortex of kittens with amblyopia [8], and that exogenous introduction of VIP increased the VIP expression in the visual cortex and elevated the PVEP amplitude [32]. Combining the ndings, VIP is critical to visual development.…”
Section: Discussionmentioning
confidence: 54%